The Implementation of ABC Classification and (Q, R) with Economic Order Quantity (EOQ) Model on the Travel Agency - Oktaviani, Anggi; Subawanto, Heru; Purba, Humiras Hardi (Bina Nusantara University, 2017)
To support customer loyalty programs, the travel agencies gave a souvenir to their customers. In one of the travel agencies in Jakarta, the demand for travel agency services could not be ensured. This had an impact on inventory items that were surplus to requirements. Inventory management was done by combining classifications ABC and (Q, R) with Economic Order Quantity (EOQ) model, which was usually used for uncertain demand. With “A” classification of the goods, two model (Q, R) scenarios were made and then simulated with software Arena. From these two scenarios, the results show that both have a tendency to decline, or the stockouts occur. However, the second scenario is more optimistic because a dummy variable is added the second scenario. Thus, the tendency is stable and does not decline.